ERROR CORRECTION MODEL ANALYSIS OF IHSG IN A MACROECONOMIC PERSPECTIVE - Vadilla Mutia Zahara,; Stannia Cahaya Suci,; Suhroji Adha, (Journal of Innovation Research and Knowledge, 2022)
An increase in the IHSG indicates that the capital market is bullish (increasing), on the other hand, if it decreases, it indicates that the capital market is bearish (decreasing). The incident was influenced by several macroeconomic factors. Among the macroeconomic factors that influence on the IHSG movement are inflation, interest rates (BI rate), Gross Domestic Product and Exchange Rates. IHSG represents all stock price movements traded on the Indonesia Stock Exchange. This study aims to determine the effect of inflation, interest rates (BI rate), Gross Domestic Product and Exchange Rates on the Composite Stock Price Index in the long and short term. Simultaneously, inflation, interest rates (BI rate), Gross Domestic Product and Exchange Rates have a significant impact in the long and short term.